Annual Plan 1979-1980 Government of Mizoram - Planning Commission (Planning Commission, 1979)
The 6th. Plan aims at settlement of 15,000 Jhumia families to permanent cultivation under Agriculture, (Horticulture & Cash Crop/W.R.C. and Seasonal Crops) and Soil Conservation Wing, (Horticulture plantation, Cash crops, Terracing for seasonal crops) Out this 15,(300 families 11,386 families, to be settled through Agriculture and the remaining 3614 families by Soil Conservation Wiring. (Annexure - 1).
Planning Department Government of Mizoram